A catalog of Nemestrinidae (Diptera: Brachycera: Nemestrinoidea) from Chile - González, Christian R.; Elgueta, Mario; Carvacho, Camila; Pañinao-Monsálvez, Laura; Barahona-Segovia, Rodrigo M. (Zootaxa, 2023)
A catalog of the Nemestrinidae from Chile is provided. Included are all valid names and synonyms for the 37 species and four genera from Chile, including information about the name, author, year of publication, page number, type species, type locality, and references. Trichophthalma Westwood is the most species-rich genus in Chile, with eighteen species, followed by Hyrmophlaeba Rondani, with twelve species. The geographical distribution of species was recorded from the examination of bibliographic data, label data on specimens in collections, and records of citizen science. Biological interactions are provided for each species when possible.